Modern trends in chemical reaction dynamics. - Yang, Xueming, 1964-; Liu, Kopin (Advanced series in physical chemistry, 2004)
The field of chemical reaction dynamics has made tremendous progressduring the last decade or so. This is due largely to the developmentof many new, state-of-the-art experimental and theoretical techniquesduring that period. It is beneficial to present these advances, boththeoretical and experimental, in a review volume published in twoparts (Parts I and II). The primary purpose of this review volume isto provide graduate students and experts in the field with a ratherdetailed picture of the current status of advanced experimental andtheoretical research in chemical reaction dynamics. All chap.